197k views
5 votes
Algebraically, find all remaining zeros of f(x) = 8x^3 - 6x^2-36x +27 in simplest form.

User Xilo
by
5.7k points

1 Answer

4 votes

Answer:


x={-(3√(2))/(2), (3)/(4), (3√(2))/(2)}

Explanation:

In order to find the zeros of a function, we must first set the equation equal to zero, so we get:


8x^(3)-6x^(2)-36x+27=0

so we can now solve this by factoring. We can factor this equation by grouping. We start by grouping the equation in pairs of terms, so we get:


(8x^(3)-6x^(2))+(-36x+27)=0

and factor each group, so we get:


2x^(2)(4x-3)-9(4x-3)=0

and now factor again, so we get:


(2x^(2)-9)(4x-3)=0

and now we set each of the factors equal to zero to find the zeros:


2x^(2)-9=0


2x^(2)=9

we divide both sides into 2 to get:


x^(2)=(9)/(2)

and take the square root to both sides to get:


x=\pm\sqrt{(9)/(2)}

which yields:


x=\pm(3)/(√(2))

We rationalize so we get:


x=\pm(3√(2))/(2)

this means that we have two zeros here:


x=(3√(2))/(2) and
x=-(3√(2))/(2)

so we take the other factor and set it equal to zero.

4x-3=0

and solve for x

4x=3


x=(3)/(4)

and that will be our third zero.

User Gorodezkiy
by
5.2k points